Differentiation of Bacillus thuringiensis From Bacilluscereus Group Using a Unique Marker Based on Real-Time PCR - Wei, Shuai; Chelliah, Ramachandran; Park, Byung-Jae; Kim, Se-Hun; Forghani, Fereidoun; Cho, Min Seok; Park, Dong-Suk; Jin, Yong-Guo; Oh, Deog-Hwan (Frontiers in Microbiology, 2019)
The efficiency of a novel biomarker (the transcriptional regulator, XRE) was tested and evaluated in differentiating Bacillus thuringiensis from Bacillus cereus group species in environmental and spiked samples based on PCR and real-time PCR. Totally 120 strains, representing 2 bacterial groups, B. cereus group and non-Bacillus sp., were used for evaluation the performance of XRE and crystal protein (cry2, an existing biomarker). Further, three diverse samples (kimbap, lettuce, and spinach) were inoculated with B. thuringiensis and prominent biomarker XRE and cry2 were used as targets. Direct analysis of the detection results for the pure cultures of B. cereus group wild-types, references and type strains revealed an accuracy rate of 97.5% targeting XRE, and 83.3% targeting cry2. The real-time PCR was constructed with a R2 value of 0.993. For the artificially contaminated samples, a concentration of 103 CFU/g of B. thuringiensis in spiked food samples could be detected using real-time PCR targeting XRE. A good performance was obtained with XRE in discriminating B. thuringiensis from B. cereus groups as well as detecting B. thuringiensis in spiked food samples with PCR or real-time PCR. Therefore, this real-time PCR targeting XRE can be used as a dependable and promising tool to identify B. thuringiensis in foods.